PENGARUH EMOTIONAL QUOTIENT TERHADAP HASIL BELAJAR AKIDAH AKHLAK SISWA KELAS VIII DI MTS AL HUSNA KOTA TANGERANG - ahmad fauzi; Khilda Tuzzahro (Universitas Muhammadiyah Tangerang, 2022)
ABSTRACTThis thesis discusses the influence of emotional quotient on the learning outcomes of moral aqidah students of class VIII MTS Al Husna. The purpose of this study was to find out 1) the description of the emotional quotient of class VIII students at MTS Al Husna, 2) the learning outcomes of class VIII morals at MTS Al Husna, 3) to examine the effect of emotional quotient on the learning outcomes of class VIII students at MTS Al Husna. This type of research is descriptive quantitative research, the approach used in this study is a quantitative approach. This research was conducted at MTS Al Husna, Tangerang city. The population in this study were all students of class VIII MTS Al Husna totaling 44 people, while the research sample used was class VIII students of MTS Al Husna. The independent variable in this study is emotional quotient, while learning outcomes are the dependent variable. The research instrument used a questionnaire scale. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis with simple regression analysis techniques. The results of the descriptive analysis showed that the emotional quotient of class VIII students at MTS Al Husna obtained an average score of 45.31 while the learning outcomes of class VIII students at MTS Al Husna obtained an average value of 44.43. The results of the inferential analysis show that the regression equation is obtained = 7.106 + 0.824X from the significant test results obtained a significant value of 0.00 where the significant value is > 0.05 (0.00 > 0.05), thus H_0 is rejected and H_a is accepted. The conclusion of this study is that there is an influence of emotional quotient on the learning outcomes of students' moral aqidah grade VIII at MTS Al Husna.